Different responses in bulk density and saturated hydraulic conductivity to soil deformation by logging machinery on a Ferralsol under native forest - Schack-Kirchner, H.; Fenner, Paulo Torres [UNESP]; Hildebrand, E. E. (Blackwell Publishing, 2007)
Ferralsols have high structural stability, although structural degradation has been observed to result from forest to tillage or pasture conversion. An experimental series of forest skidder passes in an east Amazonian natural forest was performed for testing the effects of mechanical stress during selective logging operations on a clay-rich Ferralsol under both dry and wet soil conditions. Distinct ruts formed up to 25 cm depth only under wet conditions. After nine passes the initially very low surface bulk density of between 0.69 and 0.80 g cm(-3) increased to 1.05 g cm(-3) in the wet soil and 0.92 g cm(-3) in the dry soil. Saturated hydraulic conductivities, initially > 250 mm h(-1), declined to a minimum of around 10 mm h(-1) in the wet soil after the first pass, and in the dry soil more gradually after nine passes. The contrasting response of bulk density and saturated hydraulic conductivity is explained by exposure of subsoil material at the base of the ruts where macrostructure rapidly deteriorated under wet conditions. We attribute the resultant moderately high hydraulic conductivities to the formation of stable microaggregates with fine sand to coarse silt textures. We conclude that the topsoil macrostructure of Ferralsols is subject to similar deterioration to that of Luvisols in temperate zones. The stable microstructure prevents marked compaction and decrease in hydraulic conductivity under wetter and more plastic soil conditions. However, typical tropical storms may regularly exceed the infiltration capacity of the deformed soils. In the deeper ruts water may concentrate and cause surface run-off, even in gently sloping areas. To avoid soil erosion, logging operations in sloping areas should therefore be restricted to dry soil conditions when rut formation is minimal.
Keywords: Ferralsol; Oxisol; forest operations; compaction; saturated hydraulic conductivity; microstructure; subsoil exposure